PENGARUH FINANCIAL DISTRESS, GROWTH OPPORTUNITY, DAN LITIGATION RISK TERHADAP KONSERVATISME AKUNTANSI - Fahira Alifia Pasha (2022)
This study was conducted to practically test the effect of financial distress, growth opportunity, and litigation risk on accounting conservatism. Accounting conservatism is proxied using the earnings accrual measure formula. Financial distress is measured using the Zmijewski proxy, growth opportunity using the market to book value proxy, and litigation risk using the debt to equity ratio. The object of this research is the property and real estate sector companies listed on the Indonesia Stock Exchange in 2017-2020. The sample was selected using a purposive sampling technique so that the sample obtained was 152 samples. The software used to test the hypothesis is STATA version 16. The results of this study indicate that 1) financial distress has significant positive effect on accounting conservatism; 2) growth opportunity has no significant effect on accounting conservatism; 3) litigation risk has no significant effect on accounting conservatism.